Bibliography and the doctrine of bibliosphere: the state and prospects of development - Е. A. Pleshkevich (Библиосфера, 2021)
The article is devoted to the analysis of the methodological potential of themain provisions of the Doctrine of Bibliosphere, developed by A. V. Sokolov. It is noted that its source is the concept of Noosphere by V. I. Vernadsky, which has been developed in the works of N. N. Moiseev. The basis of the Doctrine is a number of provisions. The first one concerns the nature of bibliosphere. However, in different works by A. V. Sokolov, it is defined in different ways, e.g. as part of a social space, as a national system of infrastructural book and communication systems that have developed at the industrial stage of man-made civilization, as a part of the document sphere, as a supersystem of book and communication systems that ensure the reproduction, preservation and further development of the national book culture. The second proposition concerns Bibliologos, or Book Mind, as the governing principle of Bibliosphere. The content of the third provision is devoted to the identification of the conflict between book and digital culture. The fourth and final statement is aimed at revealing the humanistic nature of Bibliosphere. It is based on ideas on the humanistic nature of book.  The existing contradictions are analyzed. Theу include, first of all, the impossibility of the direct transfer of terminology and basic provisions of the theory ofNoosphere to library and bibliographic concepts due to the difference in the scale of these theories (Noosphere and Bibliosphere), as well as the applied nature of the latter. Secondly, the contradiction highlighted by A. V. Sokolov is considered as a local problem caused by the transition to new technologies. Its resolution is not of a key nature and does not determine the vector of development of librarianship and bibliography. Third, the author questions the validity of identifying Bibliologos as a governing principle within the framework of a theory based on the principles of scientific rationality, which excludes the appeal to mysticism. Fourth, it is noted that the humanistic nature of librarianship and bibliography is given not by the nature of the book, which is indifferent, but by library and library and bibliographicactivities aimed at the humanistic development of society.   As a result of the analysis of Doctrine, the author comes to the conclusion that the idea of creating a theory, the main provisions and methodology of which allow us comprehensive consideration of social, information, technological and ethical (humanistic) aspects of librarianship and bibliography is relevant for modern library and bibliographic science in the context of the transition to a new model of organizing librarianship and bibliography. The analysis of the Doctrine on Bibliosphere has shown that it can potentially become such a theory, provided that the contradictions and unresolved issues identified by us are successfully resolved. At the same time, from a methodological point of view, it is fundamental to returnto the positions of materialism and dialectics.